Technical and operational characteristics of GPS radiosounding system in the upper air network of IMD (MAUSAM, 2011)
In recent years, the upper air radiosounding system based on Global Positioning System (GPS) is used as an effective method. GPS receiving device in a Radiosonde improves observation accuracy, allowing simplification of ground equipment. To get improved quality of upper air data, ten stations have been upgraded with new upper air systems based on GPS. This paper describes the upper air radiosounding system that adopts the GPS. After the introduction of GPS Radiosonde in the network at 10 places, data quality has improved substantially at these stations, which has been validated by National Centre for Medium Range Weather Forecasting (NCMRWF) and European Centre for Medium-Range Weather Forecasts (ECMWF). In all cases the quality change has been remarkable and as a result black list tag is removed by ECMWF for the Indian GPS stations.